Pengaruh Digital Marketing Terhadap Keputusan Pembelian Properti Dan Brand Image Sebagai Mediasi Serta WOM Sebagai Moderasi Di Perumahan Grand Wisata - Basuki, Sang Ayu Roro; Dimas Hamiarso Aji Sampurno; Kevin Andrean; Retno Purwani Setyaningrum (Jurnal Ekonomi Syariah Pelita Bangsa, 2023)
There are many ways to try and better understand the attractiveness of a property. Competition between property entrepreneurs is currently quite tight, so it is interesting to study further by testing and analyzing the influence of digital marketing on property purchasing decisions in grand tourist housing and brand image as mediation and WOM (word of mouth) as moderation. This study investigates 1) will Digital Marketing influence property purchasing decisions positively and significantly? 2) does Brand Image have a positive and significant effect on purchasing decisions, 3) does WOM have a positive and significant effect on purchasing decisions, 4) Can brand image mediate the influence of digital marketing on Purchasing Decisions? 5) Is WOM able to moderate the Effect of Digital Marketing on Property Purchase Decisions? The study for the survey used Stratified Random Sampling, by grouping by age, 100 respondents were selected via the Google form. Data were analyzed using Smart Partial Least Square (PLS) 23. The results of the study concluded that Digital Marketing had a positive and significant influence on property purchasing decisions, Brand Image had a positive and significant effect on purchasing decisions, WOM had a positive and significant effect on purchasing decisions, brand image mediates the influence of digital marketing on purchasing decisions and WOM moderates the influence of digital marketing on property purchasing decisions in grand tourist housing.